Optimization of refracturing timing for horizontal wells in tight oil reservoirs: A case study of Cretaceous Qingshankou Formation, Songliao Basin, NE China - GUO, Jianchun; TAO, Liang; ZENG, Fanhui (Petroleum exploration and development, 2019)
Tight oil reservoirs in Songliao Basin were taken as subjects and a novel idealized refracturing well concept was proposed by considering the special parameters of volume fracturing horizontal wells, the refracturing potential of candidate wells were graded and prioritized, and a production prediction model of refracturing considering the stress sensitivity was established using numerical simulation method to sort out the optimal refracturing method and timing. The simulations show that: with the same perforation clusters, the order of fracturing technologies with contribution to productivity from big to small is refracturing between existent fractured sections, orientation diversion inside fractures, extended refracturing, refracturing of existent fractures; and the later the refracturing timing, the shorter the effective time. Based on this, the prediction model of breakdown pressure considering the variation of formation pressure was used to find out the variation pattern of breakdown pressure of different positions at different production time. Through the classification of the breakdown pressure, the times of temporary plugging and diverting and the amount of temporary plugging agent were determined under the optimal refracturing timing. Daily oil production per well increased from 2.3 t/d to 16.5 t/d in the field test. The research results provide important reference for refracturing optimization design of similar tight oil reservoirs.